Analisa Quality of Services Pada Jaringan Sekolah Dengan Metode Queue Tree Studi Kasus: Lab Bahasa SMAN 47 Jakarta - Elly Mufida; Anwar Khamidi; Doni Andriansyah (Universitas Bina Sarana Informatika, 2023)
Abstract - The use of the internet with a large number of users has problems with fair and equitable use of bandwidth. The use of the internet in the computer network of SMAN 47 Jakarta is a very large number of students and teachers. Computer networks in schools are provided not only to support the teaching and learning process but also to support the very high mobility of the learning community. Of the many teachers, staff and students at SMAN 47 Jakarta who are active internet users, some users download (using the Download manager), and some use it for browsing, running YouTube, Twitter, Instagram applications, and so on. . With limited bandwidth and no regulation of bandwidth usage, causing unfair and equitable distribution of bandwidth, bandwidth management is carried out using the simple queue method, as well as to make it easier for network administrators to configure. The success of bandwidth management is carried out through Quality of Services (QOS) with indicators: throughput, jitter, packet loss and delay. The value used as a barometer of QOS success is the THIPON index. From the test results of the proposed system made by the author, a case study in the Lab room, that the implementation of bandwidth management with the simple queue method resulted in a score of 4 THIPON indexes on all measured QoS indicators. Through this bandwidth management, network administrators can provide guarantees to users on the availability and fairness of bandwidth usage according to the user's priorities and needs. It is necessary to make a Standard Operational Procedure (SOP) regarding the bandwidth management mechanism so that bandwidth management can be carried out in accordance with the standards and carried out by whoever is the network administrator.